Flower strips enhance the abundance and biocontrol services of predatory arthropods in a pear orchard - Guodong Han; Xingrui Zhang; Zhiping Cai; Yunli Xiao; Feng Ge (Biological Control)
Habitat management, such as the planting of companion plants, enhances biodiversity and biological control in agricultural systems. Here, we focused on the abundance, spillover, and biocontrol abilities of predators in pear crops with companion flower strips. Companion plant Cnidium monnieri attracted four predator species: Harmonia axyridis, Propylaea japonica, Chrysoperla sinica, and Episyrphus balteatus. Predator abundance during the full bloom stage of C. monnieri was significantly higher than during the other stages. The predator H. axyridis present on flower strips migrated to pear trees at distances of 2–18 m from the flower strips. The predators inhabiting the pear tree migrated to the flower strips after pest control; approximately 28.89 % of the predators onflower strips originated from the pear trees. Exclusion cage tests quantitatively assessed predator-mediated biological control of pear psyllids and showed that the control effect decreased as the distance from the C. monnieri strips increased. The biocontrol services index was 2.24 times higher at a distance of 2 m from the C. monnieri strips than a distance of 18 m. Our results suggest that companion plant C. monnieri enhances the predatory natural enemy population and effectively suppress the pear psyllid population in pear orchards.